Performance Reporting in the Malaysian Government - Maria Anna Mucciarone,; John Neilson, (Asian Academy of Management Journal of Accounting and Finance, 2011)
During the late 1980s, government agencies in many countries began to implement public sector management reforms to improve their efficiency and effectiveness. Many of these reforms were prompted by demands placed on governments for improved uses of public funds. In 2005, the Malaysian government and the Manpower Planning and Modernising Unit (MAMPU) circular 2/2005 introduced the concept of Key Performance Indicators (KPIs) for the public sector. Few studies have analysed these reforms in Malaysia. Based on a survey of Federal and State governments in Malaysia, this paper examines performance indicators and accountability practices and explains the hypothesised relationships between oversight bodies, political visibility and the accounting abilities of bureaucrats. Institutional theory was used to develop the theories and interpretive techniques used in this research. Multiple regression analysis was used to analyse the hypothesised relationships. This research provides an understanding of factors that influence the use of performance measures, which, in turn, could be used to formulate future government policy.